Some Efforts to Improve Business Performance Improvement Through Fishery Business Environment in Cantrang (Boat Seine) and Local Government Policies in The District Rembang - Peny Kusumawati (Saintek Perikanan : Indonesian Journal of Fisheries Science and Technology, 2010)
Fishing effort is one of economic activities so that in running its activities are always based on economic considerations for businesses that run to generate profits. Fishing effort has not been able to contribution a larger potion to develop Central Java economy. This is because the factors that affect fishing effort. Therefore, the government should take steps to of improve economic development, especially in the field of fisheries. The purpose of this study is to determine the environmental impact of fishing effort to the performance of fisheries, fishery business environment, and government policies on the performance of the fishery business in district Rembang. The research was conducted in Rembang in April - May 2008. The method used is descriptive by counducting survey. Primary sources of data the fishermen community. The method to determine the respondents by using purposive sampling method. Collected data were analyzed using descriptive statistics, the presentation of data displayed in a frequency distribution table. To test the hypothesis proposed in this research by using, data analysis technique SEM (Structural Equation Modelling) which is operated using the program AMOS 6. The results of research shows the significance level of 5% positive effect on the business environment business performance with the calculated value of t (4.468)> | 1.96 |. By lookong at, the business environment variables fisheries, fishery performance cantrang can increase the business environment has positive influence on local government policy variables with t-count value (7.017)> | 1.96 |. Government policy is able to increase fishing effort. Capital with low interest rates is able to help fishermen catch fish in running the business. Local government policy has positive influence on business performance variables in thecapture fisheries with t-count (2.311)> | 1.96 |. Capital with low interest rates can increase the performance of the fishery business in the distric of Rembang. In conclusion the fishermen to obtain capital to improve fishing business.   Key Wards : Business Environment, Performance, Government Policies